Tooth wear, growth and height in rabbits (Oryctolagus cuniculus) fed pelleted or extruded diets with or without added abrasives. Issue 3 (12th May 2021) - Martin, Louise F.; Ackermans, Nicole L.; Tollefson, Troy N.; Kircher, Patrick R.; Richter, Henning; Hummel, Jürgen; Codron, Daryl; Hatt, Jean‐Michel; Clauss, Marcus
Abstract: Among the different factors thought to affect dental wear, dietary consistency is possibly the least investigated. To understand tooth wear of herbivorous animals consuming different dietary consistencies with different abrasive potential, we fed 14 rabbits ( Oryctolagus cuniculus ) exclusively with a timothy grassmeal‐based diet in either pelleted or extruded form, or the same diets with an addition of 5% fine sand abrasives (mean size 130 µm). First, we offered the rabbits the pelleted and extruded diets as well as the pelleted control and pelleted abrasive diet in a two‐stage preference experiment. Then, the rabbits received each diet for 2 weeks in a randomised serial feeding experiment, where each animal served as its own control. Tooth measurements for wear, growth and height were achieved using a manual calliper, endoscopic examination and CT scans. The analysis of the diets as fed showed almost identical mean particle size, but the extruded diet had a lower density (volume/mass) and softer consistency compared to the pelleted one and was favoured by most rabbits. The rabbits selected against the diet with sand during the preference experiment, possibly because it caused more tooth wear, especially on the teeth most exposed to wear along the upper tooth row (upper P4 and M1). The maxillary teeth also showed evidence of an increased chewing laterality by the end of the experiment. The extruded diet led to a significantly lower cheek teeth height than the pelleted diet, potentially due to the higher chewing effort needed for a similar dry matter intake. The results suggest that dietary hardness alone is a poor predictor of dental wear. The regrowth of the teeth matched wear consistently.